Makna Pemeringkatan dan Peningkatan Kinerja Perguruan Tinggi Perspektif Intellectual Capital - Hermawan, Sigit; Sriyono, Sriyono; Hariyanto, Wiwit; Fediyanto, Niko (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 2 (2019)DO - 10.24843/JIAB.2019.v14.i02.p01, 2019)
The purpose of this research is to analyze the meaning of ratings and formulate efforts to improve the performance and competitiveness of universities in the intellectual capital perspective. The interpretive qualitative research type was used. Data collection was carried out using in-depth interviews, focus group discussions, observations, and documentation. Data analysis was carried out throughout the four-stage research process involving data collection, data reduction, data display, and conclusion. The results of the study state that the meaning of ratings is related to performance, media promotion, and related to reputation or image building. Efforts to improve the performance and competitiveness of universities can be done by optimizing the role of human capital, structural capital, and relational capital both individually and integrated as intellectual capital. Another method that can be used is the comprehensive intellectual capital management or CICM method. Keywords:  Ranking, performance, competitiveness, intellectual capital